A let-7 MicroRNA-sensitive vesicular stomatitis virus demonstrates tumor-specific replication - Bell, John C.; Atkins, Harold; Lichty, Brian D.; Brown, Christopher W.; Falls, Theresa J.; Edge, Robert E. (Université d'Ottawa | University of Ottawa, 2008)
Creation of potent oncolytic viruses (OVs) suitable for the clinic may require new strategies in virus design. Replication-competent viruses facilitate a variety of approaches to achieving tumor specificity. Altered expression of microRNAs is a common hallmark of cancer that we demonstrate can be used to alter expression of a potent wild-type viral gene to achieve tumor-specific replication of an engineered vesicular stomatitis virus (VSV). Incorporation of let-7 microRNA complementary sequences within VSV eliminates undesirable replication and associated toxicity in normal cells but permits growth in cancer cells in vitro and in vivo. This is proof of concept that viruses designed to exploit the differential microRNA expression in cancer cells is a viable approach, potentially useful in optimizing oncolytic viral gene expression for maximal antitumor activity and safety.